Effect of Short-Term Forward Head Posture Correction for Masseter Muscle Activity and Temporomandibular Joint Function for People with Upper Cross Syndrome - Ieva Masiulytė; Giedrė Jurgelaitienė; Andrius Šatas (Lithuanian Sports University, 2019)
Background. In 1996, meta-analysis of studies was performed and it showed the connections between head posture changes and temporomandibular joint (TMJ) dysfunctions (Harrison et al., 1996), but the abnormalities of the mandibular usually were treated as the only pathology leading to poor clinical eﬀect (Lee et al., 2017). Supposedly, occlusion problems are related not only to the position of the jaw and skull, but also to the shoulder and spine, which act as a biomechanical chain (Moreno, Aranza, 2013; Shousha et al., 2018). There is a lack of evidence how head posture correction changes stomatognathic system functions, that is why our study aimed to determine if a short-term head posture correction aﬀects the system. Research aim. Determine the eﬀect of short-term forward head posture correction for temporomandibular joint (TMJ) function. Research methods. Evaluation of posture, TMJ range of motion, jaw opening stereotype. Research results. After a short-term head posture correction, head inclination angle alteration was as follows: ScapularR = 5.65°, ScapularL = 3.9°. Jaw opening alteration was ScapularR 15.09 mm, ScapularL 15.58 mm. The diﬀerence between mandibular deviations decreased to ScapularR 0.32 mm; ScapularL 1.60 mm. Deviation during jaw opening reduced ScapularR 2.06 mm; ScapularL 2.38 mm. Conclusion. Short-term head posture correction signifcantly reduced head inclination angle, mandibular opening movement amplitude and deviation from the centre line in individuals with upper cross syndrome and asymmetric scapular position. Keywords: temporomandibular joint, head posture, upper cross syndrome.